Analisis Aksesibilitas Tokopedia Berbasis Mobile Menggunakan User Experience Questionnaire - Florentina Yuni Arini; Mahdi Habibi; Zahra Zakiyah Kaltsum; Muhammad Rifqi Rahman; Pramudya Kirana Mandala Putra; Samudra Azriel Pradana (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
This study aims to comprehensively examine the accessibility level and user experience of Tokopedia on mobile based on the Human-Computer Interaction (HCI) approach by employing the User Experience Questionnaire (UEQ) as the primary instrument. Data collection involved 50 active Tokopedia users, with the UEQ instrument comprising 26 statements and a 7-point response scale. Six core scales—attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty—were evaluated and analyzed by calculating the average score for each aspect and comparing it to the standard UEQ benchmark. The results demonstrate that Tokopedia excels in attractiveness, perspicuity, and efficiency, while innovation in the novelty and stimulation scales remains a challenge that requires further optimization. This study underlines the importance of UX evaluation based on HCI as a foundation for developing inclusive features to support an optimal and sustainable user experience